People in the Mountains - Pelisiak, Andrzej (Archaeopress, 2018)
This book studies current approaches to the archaeology of mountainous landscapes, presenting research results from different scientific contexts. To discuss these issues, and to study different aspects of human activity in the mountains and adjacent regions it incorporates archaeological, botanical, zooarchaeological and ethnological information.